Implementation of the Lora System for Temperature and Humidity Monitoring in POLBAN Classrooms - Arman, Muhammad; Falahuddin, Muhammad Anda; Susilawati (Jurnal Otomasi Kontrol dan Instrumentasi, 2023)
The need for temperature and humidity monitoring in classrooms, is very important for the purpose of comfortable teaching and learning processes, especially after the Covid-19 pandemic conditions. At Politeknik Negeri Bandung (POLBAN), there are more than a hundred classrooms. The rooms are spread over several buildings; therefore, the process of monitoring temperature and humidity will be difficult if it is done using a cable (wireline). In this study, a temperature and humidity monitoring system for classrooms at POLBAN will be made using LoRa wireless architecture. In several classrooms, temperature and humidity sensors will be installed combined with a LoRa sending system. There are conditioned room and unconditioned room. On the monitoring center, a LoRa receiver system is also installed. Data from each classroom, will wirelessly be sent to the monitoring center, for further processing. In the implementation stage, one gateway, 4 endnotes with DHT11 sensor are used. Testing process is carried out by verifying and monitoring performance in 4 classrooms and in open spaces. Results of verifying show a difference of 2℃ and 1% of the RH value with a reference measuring instrument. There is no difference in temperature and RH values at the endnode and gateway.